Shopping Center Design With a Responsive Architectural Approach To The Tropical Climate In The Medan City - Suwantoro, Hajar; Rahman , Abdur (Scientica: Jurnal Ilmiah Sains dan Teknologi, 2024)
The design of this shopping center is located on Mongonsidi street, Medan City, North Sumatra, Indonesia. The area on the site is in the center of Medan City, where the surrounding buildings are commercial building areas and densely populated residential areas with the population of Medan City being 2,460,858 people this year. The area on the site has the potential to be used as a place for shopping and recreation. However, this area has limited facilities and infrastructure that is not well organized, especially the lack of greenery in the form of plant vegetation. For the need for activity generators in the site location area, namely on Mongonsidi street, the design that will be created is a mall building in the form of a public business building and as a place for shopping and recreation. The design of the shopping center building uses a Tropical Architecture approach as a green open space and provides adequate lighting so that building users feel more comfortable when carrying out activities inside the building.